1998
DOI: 10.1182/blood.v92.11.3997.423k52_3997_4002
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIII (CD16)-Deficient Mice Show IgG Isotype-Dependent Protection to Experimental Autoimmune Hemolytic Anemia

Abstract: In autoimmune hemolytic anemia (AIHA), there is accumulating evidence for an involvement of FcγR expressed by phagocytic effector cells, but demonstration of a causal relationship between individual FcγRs and IgG isotypes for disease development is lacking. Although the relevance of IgG isotypes to human AIHA is limited, we could show a clear IgG isotype dependency in murine AIHA using pathogenic IgG1 (105-2H) and IgG2a (34-3C) autoreactive anti–red blood cell antibodies in mice defective for FcγRIII, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
6
31
0
1
Order By: Relevance
“…This may easily account for the strong inhibition of in vitro erythrophagocytosis obtained in this study with human IgG1 and IgG3, but not with IgG2 and IgG4, and is consistent with the in vivo activity of IgG1 and IgG3 reported previously [36]. This efficiency of IgG1 and IgG3, but not of IgG2 and IgG4, may correspond to binding to Fc γ RIII that specifically recognizes these isotypes [41] and that is involved in antibody-mediated erythrophagocytosis, at least in the mouse [42]. Because the avidity of IgG oligomers to Fc γ receptors increases with their size [43], it could be postulated that large polymers would be more efficient to block these receptors and therefore to inhibit erythrophagocytosis.…”
Section: Discussionsupporting
confidence: 90%
“…This may easily account for the strong inhibition of in vitro erythrophagocytosis obtained in this study with human IgG1 and IgG3, but not with IgG2 and IgG4, and is consistent with the in vivo activity of IgG1 and IgG3 reported previously [36]. This efficiency of IgG1 and IgG3, but not of IgG2 and IgG4, may correspond to binding to Fc γ RIII that specifically recognizes these isotypes [41] and that is involved in antibody-mediated erythrophagocytosis, at least in the mouse [42]. Because the avidity of IgG oligomers to Fc γ receptors increases with their size [43], it could be postulated that large polymers would be more efficient to block these receptors and therefore to inhibit erythrophagocytosis.…”
Section: Discussionsupporting
confidence: 90%
“…5,6 Studies in mouse models lacking various Fc receptors have demonstrated the pivotal role of Fc receptors in many IC-mediated diseases. [7][8][9][10][11] Lupus-prone mice lacking Fcc receptors I and III as a result of targeted disruption of the Fc receptor c-chain (FccR )/) ), were completely protected from glomerulonephritis. 12 Complement-deficient mice mount a normal Arthus reaction, whereas FccR-deficient mice lack this ability.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these receptors was sufficient to induce ITP, suggesting a redundant role of activating FcgR . The involvement of FcgRI, FcgRIIIA, and FcgRIV was also reported in systemic lupus erythematosus (SLE) (Seres et al, 1998), experimental hemolytic anemia (Meyer et al, 1998;Syed et al, 2009), glomerulonephritis (Fujii et al, 2003), and arthritis (Bruhns et al, 2003;Ioan-Facsinay et al, 2002;Mancardi et al, 2011). The role of FcgRI in arthritis is however controversial as the blockade of FcgRIIIA and FcgRIV in wild type mice abolished symptoms and neutrophil infiltration in the joints .…”
Section: Autoimmune Diseasesmentioning
confidence: 95%